Local Examination in Child Custody Disputes: Judges’ Efforts to Find the Best Interests of the Child - Bustanul Arifien Rusydi (Jurnal Hukum Novelty, 2023)
Introduction to The Problem: Implementation of local examinations in the provisions of Article 153 HIR, Article 180 Rbg, and Article 211 Rv is optional. The judge has the authority to determine whether it is necessary or not to carry it out. Generally, local inspections are carried out in civil cases with the object of dispute being land or fixed assets. However, it does not rule out the possibility that local examinations can also be carried out on child custody disputes because there is no limit to certain cases that can be carried out by local examinations. Some cases of child custody, some are examined by carrying out local inspections and some are not.Purpose/Objective Study: This study aims to describe the urgency of local examinations in child custody disputes, especially in ongoing cases and those that have been decided contradictory. Thus, it would exhibit the judges’ efforts in identifying and determining the best interests of the child from the course of the examination process at the trial.Design/Methodology/Approach: This study examines court decisions on child custody cases using a descriptive analysis approach in a qualitative study. This research was conducted on the basis of the efforts of judges to accommodate the interests of all parties so that research data were obtained from civil procedural law regulations, marriage laws, child protection laws, court decision documents, and related scientific journals. Data were analyzed using a normative approachFindings: In the process of proving the trial of child custody disputes, there are differences in the attitude of judges, especially in carrying out local examinations. There are judges who consider it necessary to carry out local examinations and there are also judges who do not. Indeed, in the regulation regarding local examinations it is optional, but in trials that carry out local examinations, the judge gets an important picture of how to determine the best interests of the child whose custody rights are disputed. From the two cases that have been studied, there are two important elements to determine the best interests of the child. First, regarding the significance of the social environment for children, namely regarding the environmental conditions of the father and mother. And second, regarding the significance of the child's will, namely the information obtained by the judge from the process of direct interviews with the child at his place of residence.Paper Type: Research Article